2021
DOI: 10.3390/pathogens10091097
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Analysis, Population Structure, and Characterisation of Multidrug-Resistant Klebsiella pneumoniae from the Al-Hofuf Region of Saudi Arabia

Abstract: Multidrug-resistant Klebsiella pneumoniae (MDR-KP) is a major public health problem that is globally associated with disease outbreaks and high mortality rates. As the world seeks solutions to such pathogens, global and regional surveillance is required. The aim of the present study was to examine the antimicrobial susceptibility pattern and clonal relatedness of Klebsiella pneumoniae isolates collected for a period of three years through pulse field gel electrophoresis (PFGE). Isolate IDs, antimicrobial assay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 62 publications
0
12
0
Order By: Relevance
“…8,81 K. pneumoniae is a leading cause of opportunistic healthcare-associated infections, which are increasingly complicated by the production of ESBL-enzymes by these bacteria. 12,82 In the present study, the pooled prevalence of ESBL-KP was 23%. Our result is in accordance with studies conducted in Bangladesh (25.335%) 83 and Sri Lanka (25%), 84 but higher in comparison to the study reported from Pakistan (15.25%).…”
Section: Discussionmentioning
confidence: 42%
See 1 more Smart Citation
“…8,81 K. pneumoniae is a leading cause of opportunistic healthcare-associated infections, which are increasingly complicated by the production of ESBL-enzymes by these bacteria. 12,82 In the present study, the pooled prevalence of ESBL-KP was 23%. Our result is in accordance with studies conducted in Bangladesh (25.335%) 83 and Sri Lanka (25%), 84 but higher in comparison to the study reported from Pakistan (15.25%).…”
Section: Discussionmentioning
confidence: 42%
“…8 The initial occurrences of ESBL-KP were reported in Europe in 1983 9 and the USA in 1989 10 and since then, there has been a continuous increase of K. pneumoniae-mediated cephalosporin-resistance around the world. [11][12][13] During the late 1980s, ESBL-KP outbreaks were mostly generated by TEM and SHV producers. 5,14 Recently, the CTX-M enzymesproducers have increased throughout the world.…”
Section: Introductionmentioning
confidence: 99%
“…Klebsiella pneumoniae (K. pneumoniae) is a Gram-negative encapsulated bacterium that colonizes multiple sites of the human body, including the gastrointestinal tract, respiratory tract, oral cavities, and skin [1]. K. pneumoniae is an opportunistic pathogen and a major cause of hospital-acquired infections, including bloodstream infections, urinary tract infections, and pneumonia [2].…”
Section: Introductionmentioning
confidence: 99%
“…They are also known to cause several common infections in children, including gastroenteritis, urinary tract infections, septicaemia, and neonatal meningitis [ 16 , 22 ]. It is also known that K. pneumoniae is one of the most common bacteria that causes of opportunistic healthcare-associated infections, which are made worse by its ability to produce ESBL enzymes [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%